2021
DOI: 10.1007/s11192-021-03890-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of biodiversity datasets: data reuse, citations and altmetrics

Abstract: Despite growing evidence of open biodiversity data reuse by scientists, information about how data is reused and cited is rarely openly accessible from research data repositories. This study explores data citation and reuse practices in biodiversity by using openly available metadata for 43,802 datasets indexed in the Global Biodiversity Information Facility (GBIF) and content analyses of articles citing GBIF data. Results from quantitative and content analyses suggest that even though the number of studies ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Khan et al (2020) suggest further enhancements of the Scholix schema and enrichment of Scholexplorer metadata using controlled vocabularies and the adoption of standardized data citations by journals to establish links between datasets and literature. Google Dataset Search also displays citation counts for datasets, but Khan et al (2021) found discrepancies between these numbers and the citation counts displayed by Google and by GBIF. These services can be potentially used to identify data reuse cases when they mature in the future.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Khan et al (2020) suggest further enhancements of the Scholix schema and enrichment of Scholexplorer metadata using controlled vocabularies and the adoption of standardized data citations by journals to establish links between datasets and literature. Google Dataset Search also displays citation counts for datasets, but Khan et al (2021) found discrepancies between these numbers and the citation counts displayed by Google and by GBIF. These services can be potentially used to identify data reuse cases when they mature in the future.…”
Section: Discussionmentioning
confidence: 98%
“…Sharing meaningful data can be time consuming, so researchers often want to know how their shared data is reused (Kratz & Strasser, 2015;Wallis et al, 2013). Data reuse is defined as the retrieval and use of a dataset by someone other than the originator, including the first use of data collected for a community (e.g., astronomy datasets from sky surveys: (Faniel et al, 2016) for social science data, the National Heart, Lung, and Blood Institute (NHLBI) data repository for clinical trials data (Coady et al, 2017), and the Global Biodiversity Information Facility (GBIF) for biodiversity and zoology data (Khan et al, 2021). While data reuse has been of increasing interest to the research community, most research has focused on scientists' data reuse practices rather than technological feasibility of data repositories to track secondary data reuse.…”
Section: Tracking Secondary Data Reusementioning
confidence: 99%
See 2 more Smart Citations
“…A hurdle towards the goal of integrating DNA-based occurrences into routine biological practice is the somewhat poor track record of biology when it comes to making actual research data available to begin with (e.g., Hinchliff et al 2015;Khan et al 2021). The final, published research paper is all too often seen as the sole end product of the research project in question, and little, if any, effort is made to facilitate re-interpretation and re-use of the underlying results and data for the same or other purposes (Durkin et al 2020;Abarenkov et al 2022).…”
Section: Discussion and Outlookmentioning
confidence: 99%